Black like me : the definitive Griffin estate edition, corrected from original manuscripts - Griffin, John Howard, 1920-1980. (San Antonio, Tex. : Wings Press, 2004)
Publisher's description: Studs Terkel tells us in his Foreword to the definitive Griffin Estate Edition of Black Like Me: "This is a contemporary book, you bet." Indeed, Black Like Me remains required reading in thousands of high schools and colleges for this very reason. Regardless of how much progress has been made in eliminating outright racism from American life, Black Like Me endures as a great human b6 s and humanitarian b6 s document. In our era, when "international" terrorism is most often defined in terms of a single ethnic designation and a single religion, we need to be reminded that America has been blinded by fear and racial intolerance before. As John Lennon wrote, "Living is easy with eyes closed." Black Like Me is the story of a man who opened his eyes, and helped an entire nation to do likewise.
Black like me -- Preface, 1961 -- Deep south journey, 1959 -- Photographs by Don Rutledge -- The aftermath, 1960 -- Epilogue, 1976 -- Beyond otherness, 1979 -- Afterword, 2004 / Robert Bonazzi.
Includes bibliographical references (p. 236-239).
Keywords: Griffin, John Howard, -- 1920-1980.; African Americans -- Southern States -- Social conditions; Southern States -- Race relations; Texas -- Biography